Being a Father and a Doctor - Triffletti, MD, Philip (North American Journal of Medicine and Science, 2009)
When your 18 year old daughter becomes seriously ill, should you help the medical team or be uninvolved in her care? This is the dilemma I confronted in June 2008. My daughter was suffering from mysterious symptoms. It all started on a Tuesday morning the week of her 18th birthday. We were driving to my office together and she said something odd “Dad, my vision is blurry” Diana always had normal vision unlike her myopic Dad and brother. Fortunately, the ophthalmologist in our building was available that morning so she went for an exam that showed no significant abnormalities. Then she started to develop severe back pain. She appeared very restless and uncomfortable and started to cry. I suggested she go to the emergency room or see her pediatrician..........